Devenir électeur en Tunisie. Sociologie du vote bourgeois dans un quartier résidentiel (élections à l’Assemblée nationale constituante du 23 octobre 2011) - Jérôme Heurtaux (L’Année du Maghreb)
This article presents the results of an exit poll conducted in the Ariana neighborhood of Tunis in October 2011 during National Constituent Assembly elections. The neighborhood is an upscale, suburban residential neighborhood where one might expect recently politicized voters to be engaged in celebrating their emancipation and focused on constitutional reform. Employing three angles of approach, our investigation discussed the analysis in terms of a tabula rasa approach, evaluating the logic and forms of political engagement and the assumption that after a long period of apathy voters would become be massively interested in politics. This hypothesis was not confirmed by the data. Rather, the data show political interest was motivated by something much older, even if it was updated and amplified in the revolutionary context. Not all voters embraced renewed enfranchisement with the same enthusiasm, or with the democratic effervescence reported in the press. Voter motivation was diverse and should not be reduced only to an altruistic desire of build democracy through a renewed Constituent Assembly. Finally, and with respect to the population’s presumed political homogeneity and motivation for participation, a significant proportion of voters chose candidates from the Islamist party while demonstrating substantial dispersal of choice among «modernist» parties and candidates.